Dynamics of Morbidity and Etiological Structure of Acute Respiratory Infections on the Eve and in the First Year of COVID-19 in the Irkutsk Region - N. A. Kravchenko; V. B. Kazanova; M. I. Khakimova; T. A. Gavrilova; Z. A. Zaikova; A. D. Botvinkin (Эпидемиология и вакцинопрофилактика)
Relevance. At the beginning of the pandemic, there was regional variability in incidence rates not only for COVID-19, but also for other acute respiratory infections of the upper and lower respiratory tract (ARIs). The first cases of COVID-19 in the Irkutsk region were detected two months later than the first cases in Russia, and at the beginning of the epidemic, the disease slowly spread among the local population. A retrospective analysis of ARIs monitoring is necessary to improve epidemiological surveillance. The aim of the work is to identify annual and seasonal changes in the incidence of ARIs and the circulation of respiratory viruses in the Irkutsk region before and during the first months of the epidemic of a new coronavirus infection. Materials and methods. A retrospective descriptive study was conducted based on the results of regional monitoring for 2017–2020. The analysis included records of acute infections of the upper (J06) and lower (J20-J22) respiratory tract, influenza (J10, J11), community-acquired pneumonia (J12-J16, J18) and COVID-19 (U07.1, U07.2), as well as the results of a study of 5.5 thousand samples from patients with ARIs. Respiratory viruses (n = 10) were detected using reagent kits for polymerase chain reaction (PCR) «AmpliSense® Influenza virus A/B-FL», «AmpliSense®ORVI-screen-Fl» (Russia). The distribution of incidence rates and PCR results was analyzed by years, epidemic seasons, calendar weeks, and age groups. Results. In 2020, the incidence of COVID-19 was 3180 per 100,000 population, or 7% of all cases of ARIs of the upper and lower respiratory tract (∑ARIs). In 2020, according to epidemiological service, the number of cases of acute respiratory infections decreased by 25.7%, but the number of cases of community-acquired pneumonia (CAP) increased by 83.2% (p < 0.001) compared to 2019. The incidence of CAP reached 1400 per 100,000 population. The proportion of children in the structure of CAP incidence decreased from 39.4% to 12.6% (p < 0.001), and the proportion of adults increased from 60.6% to 87.3% (p < 0.001). These changes were most pronounced during the «second wave» of COVID-19 at the end of 2020. The share of CAP in ∑ARIs on average for 2017-2020 was 2.62% (CI 2.56–2.68). This indicator was exceeded at the end of 2020 during the COVID-19 epidemic – 8.08 (CI 8.07–8.09), and also at the beginning of 2019 during the influenza epidemic – 2.83% (CI 2.81–2.85). In 2019–2020 an increase in the frequency of positive tests for human coronaviruses (hCovs) up to 2.1–2.3% was registered, compared with 0.7–0.9% in 2017–2018 (p<0.05). Rhinoviruses continued to circulate actively during the COVID-19 epidemic. A significant correspondence between the frequency of detection of viruses and the share of CAP in ARIs was established only for influenza viruses (χ2 = 26.2, p < 0.01). For other viruses, the relationship is not statistically significant (p > 0.05). Conclusions. The start of the COVID-19 epidemic was accompanied by significant changes in the incidence of ARIs, although in 2020 the number of registered cases did not exceed 10% of ARIs. The increase in the proportion of CAP in ARIs and the change in age risk groups deserve special attention. The epidemiological analysis does not confirm the hypothesis of a possible spread of SARS-Cov2 in the Irkutsk region before 2020.